Measurement of inner radiation belt electrons with kinetic energy above 1 MeV. Issue 10 (3rd October 2015) - Selesnick, R. S.
Abstract: Data from the Proton‐Electron Telescope on the Solar, Anomalous, and Magnetospheric Particle Explorer (SAMPEX) satellite, taken during 1992–2009, are analyzed for evidence of inner radiation belt electrons with kinetic energy E > 1 MeV. It is found that most of the data from a detector combination with a nominal energy threshold of 1 MeV were, in fact, caused by a chance coincidence response to lower energy electrons or high‐energy protons. In particular, there was no detection of inner belt or slot region electrons above 1 MeV following the 2003 Halloween storm injection, though they may have been present. However, by restricting data to a less‐stable, low‐altitude trapping region, a persistent presence of inner belt electrons in the energy range 1 to 1.6 MeV is demonstrated. Their soft, exponential energy spectra are consistent with extrapolation of lower energy measurements. Key Points: Inner radiation belt electrons were measured by SAMPEX/PET during 1992–2009 Following the 2003 Halloween storm they were not observed above 1 MeV but may have been present Less stably trapped electrons were seen at other times with soft energy spectra up to 1.6 MeV